Limits of Authority and Competence of General Practitioners in Aesthetic Practice - Nazliyah, Inayatun; Putera, Andika Persada; Zamroni, Mohammad (CV. Publikasi Indonesia, 2025)
The rapid development of medical aesthetic services that is not matched by the creation of governing regulations has become one of the most important issues in the field of aesthetic medicine, namely competency issues related to authority because there are still gray areas regarding the authority of general practitioners in aesthetic practice. This research aims to analyze the authority of general practitioners in aesthetic practice and legal protection for general practitioners in aesthetic practice. The research methodology used in writing this thesis is normative juridical. This approach uses a statue approach, conceptual approach, and comparative approach. The authority and competence of general practitioners in aesthetic services are limited to primary care, non-invasive, minimally invasive procedures and are only allowed to perform medical procedures in accordance with what has been obtained during the education process, and are advised to conduct additional training and make referrals to specialists if not their authority and competence. Legal protection for general practitioners in aesthetic medicine services, general practitioners must apply professional standards and standard operating procedures in carrying out aesthetic medical services is widely regulated in laws and regulations.